Review of two genera of Nirvanini leafhoppers (Hemiptera: Cicadellidae: Evacanthinae) from Africa - Wang, Yang; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2017)
Two Nirvanini genera, Afronirvana Evans and Afrokana Heller, including two new species, Afronirvana leptoclada sp. nov. and Afrokana transmaculata, sp. nov. from Africa are described. One new combination, Afronirvana africana (Heller) n. comb., is proposed. The female genitalia of these two genera are described and illustrated for the first time. Afronirvana and Afrokana are similar to the Oriental Kana Distant (= Yaoundea Linnavuori, syn. nov. with K. semela (Linnavuori), n. comb.) in having the aedeagus straight through most of its length but with a posteroventrally curved distal section that is strongly appressed to the shaft. Descriptions, illustrations and a key to species of Afronirvana and Afrokana are provided.